Mūhndsīn; explorations of the right to the city - Saber, Fatma (AUC Knowledge Fountain, 2016)
With the majority of the world’s population living in cities, the urban has become a dynamic space where contemporary social relations, gender roles and subjectivities are being recreated. This thesis explores the nexus between the urban and the social spaces it creates, with a specific focus on Cairo. It adopts critical urban theory and the right to the city as theoretical approaches to understanding these dynamics by studying Mūhndsīn a district in the city which combines diverse forms of living and dwelling. The thesis reaches conclusions on the operationalization of the right to the city by focusing on three themes of significance, which are the evolution of the built environment,visibility in the urban and neo-liberalization of space. These areas of study reveal the impact of the urban on the social, reaching conclusions on the possibilities of political action which go beyond conventional activism and resistance. It argues that participation and appropriation of space are the paths towards a city yet to come.